WACANA BAHASA INDONESIA DAN PENGAJARANNYA - Wahyono, Hari . (Majalah Transformatika, 2009)
Discorse is part of linguistic study. As a linguistic! study, discourse is placedin the highest Rank Discourse study includes sentence, phrase, clause, paragraph, .fragment and complete discourse. The discourse can be analyzed from the various point ofÂ view, for examples an analysis of discourse element and sentence analysis. Discourse analysis is one materials applied in teaching discourse, we can aply either deuctive or inductive pattern (model) Key Word: discourse, linguistics, teaching, deductive, inductive